Drosophila melanogaster Model for Recent Advances in Genetics and Therapeutics - Khan Perveen, Farzana (IntechOpen, 2018)
This book contains 12 chapters divided into two sections. Section 1 is "Drosophila - Model for Genetics." It covers introduction, chromosomal polymorphism, polytene chromosomes, chromosomal inversion, chromosomal evolution, cell cycle regulators in meiosis and nongenetic transgenerational inheritance in Drosophila. It also includes ecological genetics, wild-type strains, morphometric analysis, cytostatics, frequencies of early and late embryonic lethals (EEL and LEL) and mosaic imaginal discs of Drosophila for genetic analysis in biomedical research. Section 2 is "Drosophila - Model for Therapeutics." It explains Drosophila as model for human diseases, neurodegeneration, heart-kidney metabolic disorders, cancer, pathophysiology of Parkinson's disease, dopamine, neuroprotective therapeutics, mitochondrial dysfunction and translational research. It also covers Drosophila role in ubiquitin-carboxyl-terminal hydrolase-L1 (UCH-L1) protein, eye development, anti-dUCH antibody, neuropathy target esterase (NTE), organophosphorous compound-induced delayed neuropathy (OPIDN) and hereditary spastic paraplegia (HSP). It also includes substrate specificities, kinetic parameters of recombinant glutathione S-transferases E6 and E7 (DmGSTE6 and DmGSTE7), detoxification and insecticidal resistance and antiviral immunity in Drosophila.